Toll-Like Receptor 4 Signaling in the Trabecular Meshwork - Mzyk, Philip; Hernandez, Humberto; Le, Thanh; Ramirez, Jose Ricardo; McDowell, Colleen M. (Frontiers in Cell and Developmental Biology, 2022)
Primary open-angle glaucoma (POAG) is one of the leading causes of blindness worldwide. With limited therapeutics targeting the pathogenesis at the trabecular meshwork (TM), there is a great need for identifying potential new targets. Recent evidence has implicated Toll-like receptor 4 (TLR4) and it’s signaling pathway in augmenting the effects of transforming growth factor beta-2 (TGFβ2) and downstream ECM production. In this review, we examine the role of TLR4 signaling in the TM and the interplay between endogenous activators of TLR4 (damage-associated molecular patterns (DAMPs)), extracellular matrix (ECM), and the effect on intraocular pressure (IOP).